2020
DOI: 10.3390/ani10010116
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate Dairy Calf Feeding from Birth to Weaning: “It’s an Investment for the Future”

Abstract: Dairy calves must be fed appropriately to meet their nutritional needs, supporting optimal growth and development to achieve the recommended target age at first calving (AFC) of 24 months. Traditional restricted milk feeding practices suppress growth, contribute to negative welfare states and may result in malnutrition and immunosuppression. Despite more recent recommendations to increase milk allowances for pre-weaned calves, restricted feeding remains a common practice. This study explored the rationales beh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 61 publications
3
37
0
1
Order By: Relevance
“…a,b,c Different superscript in a single row indicates a significant difference ; * = Significant at 5% level; NS = Non significant It is revealed from the study that dry matter intake of calves increasing significantly. The obtained results supported by the findings of Palczynski et al (2020) and Sudhakar et al (2002). Palczynski et al (2020) reported that balanced feed supplementation with UMB increased daily dry matter intake and Sudhakar et al (2002) observed significant difference (p>0.01) in average daily dry matter intake in buffaloes fed UMMB supplemented ration.…”
Section: Effect Of Dry Matter Intake (Dmi) On Calvessupporting
confidence: 89%
See 1 more Smart Citation
“…a,b,c Different superscript in a single row indicates a significant difference ; * = Significant at 5% level; NS = Non significant It is revealed from the study that dry matter intake of calves increasing significantly. The obtained results supported by the findings of Palczynski et al (2020) and Sudhakar et al (2002). Palczynski et al (2020) reported that balanced feed supplementation with UMB increased daily dry matter intake and Sudhakar et al (2002) observed significant difference (p>0.01) in average daily dry matter intake in buffaloes fed UMMB supplemented ration.…”
Section: Effect Of Dry Matter Intake (Dmi) On Calvessupporting
confidence: 89%
“…The obtained results supported by the findings of Palczynski et al (2020) and Sudhakar et al (2002). Palczynski et al (2020) reported that balanced feed supplementation with UMB increased daily dry matter intake and Sudhakar et al (2002) observed significant difference (p>0.01) in average daily dry matter intake in buffaloes fed UMMB supplemented ration. Prasad and Agarwal (1996) worked with 18 crossbred heifers and CP content of concentrate mixture fed to group T 1 , T 2 and T 3 was 24, 28 and 32% respectively.…”
Section: Effect Of Dry Matter Intake (Dmi) On Calvessupporting
confidence: 89%
“…There is evidence of discrimination against male compared to female dairy calves in several areas (6,48,67,71). In particular colostrum and post-colostrum feeding practices differ between males and females in many countries [Canada: (72,73); United States; (71); New Zealand: (48); Ireland: (69) and UK: (74)]. This can be associated with differential rates of failure of passive transfer (FPT) of immunologlobulins between male and female calves (75,76).…”
Section: Management Of Male Compared To Female Calves On Farmmentioning
confidence: 99%
“…Finally, and not less important than ensuring adequate colostrum feeding, is the adequacy of the feeding program of those calves before been sold and transported to the rearing farm or auction market. In a recent paper that summarized interviews with dairy farmers in England [ 41 ] it was highlighted that dairy farms often do not feed calves according to the recommended best practice despite the legislation and technical advisory efforts. Surprisingly, despite the huge amount of studies and reviews published in recent years that evaluate different calves’ feeding strategies on performance and health [ 42 , 43 , 44 , 45 ], these authors indicate that advisors were concerned because calves are commonly underfed, probably because there are insufficient clear recommendations.…”
Section: Nutrition Of Unweaned Calves’ Previous To the Arrival To mentioning
confidence: 99%